2006
DOI: 10.1080/00207450500442288
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Acute and Regular Exercise on Intraocular Pressure in Turkish Athlete and Sedentarians

Abstract: The aim of this study was to investigate the changes that take place in IOP in athletes and people leading sedentary lives subjected to aerobic and anaerobic exercise and how chronic exercise could affect these changes. The study included 20 sportsmen (Group 1), and 20 people leading sedentary lives (Group 2). The intensity of the exercise for both groups was determined according to the Karvonen protocol and executed as an aerobic exercise program involving running on a treadmill for 30 min. Subjects in both g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 16 publications
2
17
0
9
Order By: Relevance
“…[26][27][28] In our results, patients on pharmacological glaucoma therapy could still obtain 5.72 ± 3.34 mm Hg IOP decrease after exercise. There was a significant IOP decrease after dynamic exercise.…”
Section: Discussionsupporting
confidence: 55%
“…[26][27][28] In our results, patients on pharmacological glaucoma therapy could still obtain 5.72 ± 3.34 mm Hg IOP decrease after exercise. There was a significant IOP decrease after dynamic exercise.…”
Section: Discussionsupporting
confidence: 55%
“…In numerous studies, intraocular pressure (IOP) has been shown to decrease in humans during exercise as summarized in a recent review article . This has been shown with conditions of acute dynamic exercise, continuous strenuous exercise, isometric exercise, and even brisk walking . Dynamic exercise has been shown to have greater IOP‐lowering effects than isometric exercise, with intensity of exercise being the most closely associated parameter with IOP reduction .…”
Section: Introductionmentioning
confidence: 99%
“…De fato, em sedentários submetidos a exercício agudo ocorreu diminuição da PIO a qual permaneceu baixa até 2 horas após a interrupção do exercício, diferente dos praticantes de exercícios que apresentam aumento da PIO imediatamente após o término do exercício e redução iniciando após 30 minutos do término (10) . Na prática de exercícios aeróbios esta diminuição é mais evidente do que nos exercícios anaeróbios, tanto para praticantes de exercícios quanto para sedentários (11) . A maior diminuição da PIO com exercícios dinâmicos do que com os isométricos foi motivo para indicá-los como coadjuvantes no tratamento de pacientes com glaucoma (12) .…”
Section: Introductionunclassified